Pornographic image detection and system - LIU ZHIJUN; HE ZHENHAI; YANG BIN (2017)
The invention provides a pornographic image detection and a system and is applied to the field of communication. At least one to-be-detected image is acquired from a high throughout business interface; at least one detection module is determined from a plurality of detection modules to work as a to-be-detected module; the to-be-detected image is sent to a corresponding to-be-detected module; and pornographic image detection is conducted for the to-be-detected image by the to-be-detected module, so a detection result is achieved. Compared with the prior art, pornographic image detection can be conducted for a plenty of images in the high throughout business; further potential safety danger of pornographic spread via the high throughout business can be avoided; and network safety of the high throughout business can be enhanced, and user experience can be improved. 本发明提供的色情图像检测方法和系统，应用于通信领域。从高吞吐量业务接口获取至少个待检测图像；从多个检测模块中确定出至少个检测模块作为待检测模块；将所述待检测图像分发给对应的所述待检测模块；所述待检测模块对所述待检测图像进行色情图像检测得到检测结果。与现有技术相比，能够对高吞吐量业务中的大量图片进行